Cross-reactive neutralizing antibody epitopes against Enterovirus 71 identified by an in silico approach - Kirk, Kristin; Poh, Chit Laa *; Fecondo, John; Pourianfar, Hamid Reza; Shaw, J.; Grollo, Lara (Elsevier, 2012)
Currently, infections of hand, foot and mouth disease HFMD) due to Human Enterovirus 71 (EV71) cannot be prevented or treated, as there are no suitable vaccines or antiviral drugs. This study aimed to identify potential vaccine candidates for EV71 using in silico analysis of its viral capsid proteins. A combined in silico approach utilizing computational hidden Markov model (HMM), propensity scale algorithm, and artificial learning, identified three 15-mer structurally conserved B-cell epitope candidates lying within the EV71 capsid proteins. Peptide vaccine candidates incorporating a target B-cell epitope and a promiscuous T-cell epitope from the related polio virus were synthesized using solid-phase Fmoc chemistry. Inbred BALB/C mice which were inoculated with two 10μg doses of the synthetic peptide, generated anti-peptide antibodies. Purified IgG isolated from pooled sera of the inoculated mice neutralized EV71 infections in vitro. Furthermore, these neutralizing antibodies were cross-reactive against other members of the Picornaviridae family, demonstrating greater than 50% virus neutralization. This indicates that the current approach is promising for the development of synthetic peptide-based vaccine candidates against Picornaviridae. Development of effective vaccines is of paramount importance in managing the disease in the Asia Pacific regions where this virus is endemic and has significant social, economic and public health ramifications.